Exhaustive ethnobotanical survey of medicinal plants used to prevent the COVID-19 epidemic in Souk Ahras province, Algeria - Gherairia, Nesrine; Boukerche, Soumaya; Chefrour, Azzedine; Boutabia, Lamia (Ethnobotany Research and Applications, 2025)
Background: The COVID-19 pandemic has posed significant global health challenges, prompting renewed interest in traditional medicine as a complementary approach. This study documents the use of medicinal plants in Souk Ahras Province, Algeria, through an ethnobotanical survey conducted in 2021/2022 among 47 herbalists. The survey aimed to assess the relevance and effectiveness of these plants in managing COVID-19 symptoms. Methods: Data were collected through semi-structured interviews, and the herbalists' knowledge was quantified using ethnobotanical indices. Principal Component Analysis (PCA) was conducted to assess the impact of socio-demographic factors on ethnobotanical Knowledge. Results: The study identified 26 medicinal plants from 17 botanical families used by herbalists in Souk Ahras Province. The most commonly cited families were Lamiaceae and Zingiberaceae, with Syzygium aromaticum and Zingiber officinale emerging as the most frequently cited species, achieving an FC of 44 and an FCR of 0.92. Key symptoms targeted included cough (ICF = 0.96), immunity boosting (ICF = 0.95), body aches, and anosmia (ICF = 0.93 each). Rhizomes (CPP = 0.40) were the most commonly used plant parts, while infusion (CMU = 0.58) was the preferred preparation method. PCA results showed that age and professional experience are key factors in acquiring and retaining ethnobotanical knowledge, while higher education levels may contribute to its decline. Conclusions: This study emphasizes the significance of traditional medicine in tackling modern health challenges and highlights the potential of these remedies as complementary alternatives to conventional therapies for COVID-19. Additional research is required to confirm their efficacy and safety. Keywords: Ethnobotany; COVID-19; herbalists; medicinal plants; ethnobotanical indices; PCA; Algeria.